2023
DOI: 10.1073/pnas.2311583120
|View full text |Cite
|
Sign up to set email alerts
|

Photonic crystals built by time in ancient Roman glass

Giulia Guidetti,
Roberta Zanini,
Giulia Franceschin
et al.

Abstract: Ancient glass objects typically show distinctive effects of deterioration as a result of environmentally induced physicochemical transformations of their surface over time. Iridescence is one of the distinctive signatures of aging that is most commonly found on excavated glass. In this work, we present an ancient glass fragment that exhibits structural color through surface weathering resulting in iridescent patinas caused by silica reprecipitation in nanoscale lamellae. This archaeological artifact reveals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In a previous study, 20 the sample was identified as a fragment of a Roman glass object using laser ablation – inductively coupled plasma – mass spectroscopy (LA-ICP-MS). This analysis revealed that the unaltered core of the glass had a silica-soda-lime high-magnesium (HMG) composition.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, 20 the sample was identified as a fragment of a Roman glass object using laser ablation – inductively coupled plasma – mass spectroscopy (LA-ICP-MS). This analysis revealed that the unaltered core of the glass had a silica-soda-lime high-magnesium (HMG) composition.…”
Section: Methodsmentioning
confidence: 99%
“…Now, after subjecting the shard to a string of Photograph of the glass shard from Aquileia. Credit: CCHT-IIT, courtesy of National Archeological Museum of Aquileia/Italian Ministry of Culture chemical and physical tests, Giulia Guidetti of Tufts University, Massachusetts, and her collaborators have identified the origin of the shard's appearance: a chemical transformation of the amorphous glass into a nanolayered material, a photonic crystal [1].…”
mentioning
confidence: 99%